2017
DOI: 10.1371/journal.pone.0176360
|View full text |Cite
|
Sign up to set email alerts
|

The influence of climatic variation and density on the survival of an insular passerine Zosterops lateralis

Abstract: Understanding the influence of environmental factors on population dynamics is fundamental to many areas in biology. Survival is a key factor of population biology, as it is thought to be the predominant driver of growth in long-lived passerines, which can be influenced by both biotic and abiotic environmental conditions. We used mark-recapture methods and generalized linear mixed models to test the influence of density and climatic variation, measured at a regional and local scale (Southern Oscillation Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The mean population fitness (λ) was obtained by multiplying the average number of fledglings of observed clutches by the mean survival during the summer, autumn and winter of young individuals along with the generation time (Table S1). These parameter values were obtained from literature ( Kikkawa and Wilson 1983 , Brook and Kikkawa 1998 , Clegg et al 2002b , Sandvig et al 2017 ). Male fitness was then scaled such that the total sum of male fitness equalled the total sum of female fitness.…”
Section: Methodsmentioning
confidence: 99%
“…The mean population fitness (λ) was obtained by multiplying the average number of fledglings of observed clutches by the mean survival during the summer, autumn and winter of young individuals along with the generation time (Table S1). These parameter values were obtained from literature ( Kikkawa and Wilson 1983 , Brook and Kikkawa 1998 , Clegg et al 2002b , Sandvig et al 2017 ). Male fitness was then scaled such that the total sum of male fitness equalled the total sum of female fitness.…”
Section: Methodsmentioning
confidence: 99%
“…Sandvig et al. () found that survival of Zosteropos lateralis on a small island near Australia was indeed correlated to climatic (rainfall) variables. Additionally, Olson et al.…”
Section: Discussionmentioning
confidence: 99%
“…The climatic variation between the species' habitats should favor unique morphological and physiological adaptations, and it is possible that hybrids would suffer from being poorly adapted to either environment. Sandvig et al (2017) found that survival of Zosteropos lateralis on a small island near Australia was indeed correlated to climatic (rainfall) variables. Additionally, Olson et al (2010) found that hybrid chickadees (hybrids of Poecile atricapillus and Poecile carolinensis) had reduced metabolic efficiency compared to their parental species, and suggested that genetic incompatibilities between mismatched mtDNA and nuclear DNA could have severe physiological costs in hybrid birds.…”
Section: Reproductive Barriersmentioning
confidence: 93%
“…2019). In contrast, in areas of high rainfall, such as the Cape Horn rainforests, very high levels of rainfall can limit the habitat use of birds (Santillan et al 2018) and decrease chick survival (Sandvig et al 2017;Schöll and Hille 2020). In places with extremely high rainfall, a decrease in structural complexity of forests could also influence a lower species richness (Rozzi et al 2007).…”
Section: The Impact Of Increasing Precipitation On the Hygric Nichementioning
confidence: 99%